Drivers of Economic Growth in South Asia: An Empirical Panel Data Study - Sapkota, Pitambar (KMC Journal, 2025)
Economic growth is the outcome of different factors as foreign direct investment, gross capital formation, size of population, government expenditure, technological improvement, rate of inflation and many others. Therefore, this study attempts to analyze the effects of foreign direct investment, gross capital formation, government expenditure, population growth rate and inflation rate on growth rate of gross domestic product (i.e. economic growth rate) of South Asia except the Maldives, through descriptive and causal research design. Panel data were taken from the World Bank data statistics between the periods of 2001 to 2023 AD. Data were analyzed by using fixed effect model on the basis of Redundant Fixed Effects Tests and Hausman Test. The study finds that population growth rate and gross capital formation positively affect the economic growth of South Asia, whereas there has been negative effect of foreign direct investment, government expenditure and inflation rate on economic growth. The study concludes that there is a critical role of population growth rate and capital formation in fostering economic growth in South Asia, with miner effect of foreign direct investment. Policymakers are advised to focus on enhancing capital investments and leveraging population growth dynamics to achieve sustainable economic growth.